THE "DIVINE PROVIDENCE" AND "THE GATEWAY OF THE STRAIT" OF MAGELLAN IN TWO COLONIAL POEMS - Formoso Bavich, Christian (My University, 2019)
Within the few representations of Spanish endeavors in the far south of the Americas, we find in Armas Antarticas by Juan de Miramontes Zuazola (1609), and Vida de Santa Rosa by the Count of La Granja (1711), two epic poems that, addressing them partially, include representations of the Strait of Magellan. This article explores these representations in dialogue with the recreations that the same works offer of Lima and the viceroyalty of Peru. I claim that both poems coincide with representing the Strait as an "other" place, whose failed fortification from Sarmiento de Gamboa's experience ends up transforming it into a nature and geography. These features condense the demonic, and their dispositions can cause unrest, and even defeat, the venture of Christianity in the New World. Since Pigafetta, indigenous people were associated to the adoration of the Devil. Here, from one poem to the other, the aborigines vanish until they disappear. That configures in the Strait a locus diabolicus without "mediators". Similarly, I explore the possibilities that this representation of the Magellan territory was built in a functional way to the capital of the viceroyalty, whose nature and religious experience sustain the fortification of the Spanish empire in America.
Keywords: strait of magellan; miramontes zuazola; conde de la granja